2001
DOI: 10.1055/s-0037-1616733
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CD40/CD40 Ligand Interactions Prevents Induction of Factor VIII Inhibitors in Hemophilic Mice but Does not Induce Lasting Immune Tolerance

Abstract: SummaryPatients with severe hemophilia A frequently develop neutralizing anti-factor VIII antibodies after replacement therapy with factor VIII (FVIII). In a search for new strategies to induce immune tolerance against FVIII in these patients, we used a murine model of hemophilia A to investigate the importance of CD40/CD40 ligand (CD40L) interactions for the initiation of the anti-FVIII immune response. We focused our attention in particular on the induction of neutralizing anti-FVIII antibodies and the Th1/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 32 publications
(29 reference statements)
2
72
0
3
Order By: Relevance
“…[31][32][33][34] The E16 knock-out hemophilia A mice used in this study, along with the genetically similar, phenotypically indistinguishable E17 knock-out mice, develop immune responses to human fVIII that require CD4 ϩ T-cell help 31,32,34 and B7/CD28 and CD40/CD40L costimulation pathways. [35][36][37][38] IgG1, IgG2a, and IgG2b anti-fVIII antibodies are produced, indicating a combined T H 1 and T H 2 response. 34,37-39 fVIII-specific interferon-␥ ϩ (IFN-␥ ϩ ), 38 interleukin-4 ϩ (IL-4), 34 and IL-10 ϩ T cells 34,38 have been identified in immunized mice, which also is consistent with a combined T H 1 and T H 2 response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] The E16 knock-out hemophilia A mice used in this study, along with the genetically similar, phenotypically indistinguishable E17 knock-out mice, develop immune responses to human fVIII that require CD4 ϩ T-cell help 31,32,34 and B7/CD28 and CD40/CD40L costimulation pathways. [35][36][37][38] IgG1, IgG2a, and IgG2b anti-fVIII antibodies are produced, indicating a combined T H 1 and T H 2 response. 34,37-39 fVIII-specific interferon-␥ ϩ (IFN-␥ ϩ ), 38 interleukin-4 ϩ (IL-4), 34 and IL-10 ϩ T cells 34,38 have been identified in immunized mice, which also is consistent with a combined T H 1 and T H 2 response.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] IgG1, IgG2a, and IgG2b anti-fVIII antibodies are produced, indicating a combined T H 1 and T H 2 response. 34,37-39 fVIII-specific interferon-␥ ϩ (IFN-␥ ϩ ), 38 interleukin-4 ϩ (IL-4), 34 and IL-10 ϩ T cells 34,38 have been identified in immunized mice, which also is consistent with a combined T H 1 and T H 2 response. In human hemophilia A, anti-fVIII antibodies are a mixture of IgG1, IgG2, and IgG4 antibodies, [40][41][42][43] again indicating a combined T H 1 and T H 2 response.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was also seen when the experiment was independently repeated with the more complete B-cell depletion using IgG2a anti-CD20 ( Figure 2D). It is known that inhibitor formation is T cell-dependent in both humans and mice, 6,[18][19][20] and it has been reported that B cells are required for optimal CD4 T-cell function. 21 Thus, the elimination of the majority of B cells may be responsible for the lack of boosting.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18] The protein B7, which is expressed on the surface of antigen-presenting cells, interacts with CD28 expressed on T cells, thereby activating T-cell proliferation and promoting the humoral response to FVIII. 14,17 Cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) is a second high-affinity T-cell receptor for the B7 ligand, and is a negative regulatory of T-cell activation.…”
Section: Introductionmentioning
confidence: 99%